UTILIZATION OF POULTRY WHOLE CARCASS MEAL AS A SUBSTITUTE FOR FISH MEAL IN THE DIETS OF GROWING PIGS - J. Ramesh; A. Gopinathan; S.M.K. Karthickeyan; V. Chandirasekaran; T. Sivakumar; S.N. Sivaselvam (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological experiment was conducted to study utilization of poultry whole carcass meal, as protein supplement in pig rations. Eighteen weaned Large White Yorkshire growing pigs were randomly divided in to three groups, having six pigs in each group viz., T1 (Control ; pigs fed with balanced grower ration containing dry fish as animal origin protein source), T2 (pigs fed with balanced grower ration containing 5% poultry whole carcass meal) and T3 (pigs fed with balanced grower ration containing 10% poultry whole carcass meal). All experimental diets were iso-caloric iso-nitrogenous; and were fed adlibitum to all pigs (T1, T2 and T3 groups) throughout the experimental period of 2 to 8 months of age and general performance of pigs was recorded. Total body weight gained (kg.) during experimental period was significantly (P<0.05) higher in pigs under T2 as compared to pigs under treatments T1 and T3 ; The total feed intake (kg) and feed efficiency during experimental period (180 days) did not differ significantly amongst treatment groups. The decrease in cost of feeding for each kg. weight gain was 4.86 and 10.62 percent in pigs fed experimental diets containing PWCM @ 5 (T2) and 10 percent (T3) levels. From this study, it was concluded that, poultry whole carcass meal can be incorporated in grower rations of pigs at 5% level without any depression in feed intake and feed.